Prevalence of resistance to nevirapine in mothers and children after single-dose exposure to prevent vertical transmission of HIV-1: a meta-analysis. - (:unkn) unknown (My University, 2007)
BACKGROUND: Single-dose nevirapine (NVP) is the main option for the prevention of mother-to-child transmission (PMTCT) of HIV-1 in countries with limited resources. However, the use of single-dose NVP results in HIV-1 viral resistance which could compromise the success of subsequent treatment of mother and child with antiretroviral combinations that include non-nucleosidic-reverse-transcriptase inhibitors. This systematic review and meta-analysis of summarized data aimed to estimate the proportion of mothers and children with NVP resistance mutations detected in plasma samples 4-8 weeks postpartum after single-dose NVP use for PMTCT. METHODS: Systematic search of electronic databases (MEDLINE, PASCAL) and conference proceedings (1997 to February 2006). Inclusion of all studies, without design, place or language restrictions, meeting the following criteria: use of single-dose NVP; viral genotyping performed with standard sequence analyses, between 4 and 8 weeks postpartum, in plasma samples; available public report; report of mothers' median baseline plasma HIV-1 RNA levels. Data extraction by two independent reviewers using a standardized form created for this purpose. Logistic random effect models to obtain pooled estimates. Univariable and multivariable meta-regression to explore sources of heterogeneity. RESULTS: The pooled estimate of NVP resistance prevalence was 35.7% [95% confidence interval (CI) 23.0-50.6] in women in 10 study arms using single-dose NVP +/- other antepartum antiretrovirals and 4.5% (CI 2.1-9.4) in three study arms providing also postpartum antiretrovirals (adjusted odds ratio 0.08; CI 0.04-0.16). The corresponding estimates in children were 52.6% (CI 37.7-67.0) in seven study arms using single-dose NVP only and 16.5% (CI 8.9-28.3) in eight study arms combining single-dose NVP with other antiretrovirals. CONCLUSIONS: Single-dose NVP is widely used for PMTCT in resource-poor settings, but the burden of viral resistance is high in
Keywords: African Research